Possibility of using the botanical insecticide azadirachtin and synthetic and semi-synthetic insecticides to control Helicoverpa armigera in sweet pepper - Tamaš Nenad D.; Sretenović Marko Ž.; Miletić Novica M. (Journal of Agricultural Sciences (Belgrade))
During 2019 and 2020, field experiments were performed on sweet pepper crops to determine the efficacy of chemical insecticides (lambdacyhalothrin, flubendiamide), semi-synthetic (emamectin benzoate), and biological pesticide (azadirachtin) in controlling cotton bollworm (Helicoverpa armigera). The experiments were performed in a randomized complete block design with four replications according to the standard EPPO method at the site of Veliko Gradište (Serbia). Flubendiamide was applied at a rate of 50 g/ha, lambda-cyhalothrin at a rate of 7.5 g/ha, emamectin benzoate at a rate of 375 g/ha, and azadirachtin at a rate of 0.75 g/ha. The intensity of the 2nd generation cotton bollworm infestation on sweet pepper at this locality was higher during 2020 compared to 2019. After performing two treatments for the 2nd generation, flubendiamide showed the highest efficacy, ranging from 92.42% (3 days after treatment - DAT, 2020) to 95.56% (9DAT, 2019). Lambda-cyhalothrin had a satisfactory efficacy in the range of 81.93% (9DAT, 2020) to 90.63% (3DAT, 2019), and emamectin benzoate showed similar efficacy from 80.72% (9DAT, 2020) to 90.63% (3DAT, 2019). Azadirachtin could gain a significant place as a botanical insecticide in integrated pest management programs for sweet pepper protection from H. armigera. However, it statistically showed a significantly lower efficacy than other insecticides (77.27%: 3DAT, 2020 to 86.67%: 9DAT, 2019).